ANALISIS KESIAPTERAPAN PENGGUNAAN SOFTWARE AKUNTANSI - Rusli Amrul; Sigit Ary Wijayanto (Jurnal Ilmiah Manajemen "E M O R", 2019)
This study aims to prove empirically the effect of information system service quality on the satisfaction of end-user accounting software, to prove empirically the effect of information system quality on end-user satisfaction accounting software and to prove empirically the simultaneous influence of service quality and information systems on end-user satisfaction accounting software. The population in this study were all NGO staff Partners of the Spiritia Foundation throughout Indonesia, totaling 23 NGOs. While the study sample used purposive sampling, namely the sample selected based on criteria. The criteria of respondents in this study were staff who were directly involved in the use of FINA accounting software and who authorized the reports produced by FINA namely Finance Staff and NGO Leaders, Spiritia Foundation Partners. The results of this study are that the quality of information system services has no significant effect on end-user satisfaction accounting software, information system quality has a significant effect on end user satisfaction accounting software and service quality and information systems simultaneously have a significant effect on accounting software user satisfaction.